Intelligent computing for sustainable energy and environment : Second International Conference, ICSEE 2012, Shanghai, China, September 12-13, 2012. Revised Selected Papers - Li, Shaoyuan; Li, Dewei; Niu, Qun; Li, Kang (Communications in computer and information science, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2012, held in Shanghai, China, in September 2012. The 60 full papers presented were carefully reviewed and selected from numerous submissions and present theories and methodologies as well as the emerging applications of intelligent computing in sustainable energy and environment.